VALUES APPLIED IN EDUCATION FIELD CONTAINED IN TOTTO-CHAN NOVEL WRITTEN BY TETSUKO KUROYANAGI - Aster Pasha (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2020)
Literary works can be created starting from the observation or experience of an author, who cares about social phenomena around her. Many literary works are inspired by social phenomena, but also do not rule out the possibility of literary works that inspire people to create certain social phenomena. It is like the story in the novel Totto-chan, Little Girl in the Window, a story about the phenomenon of education in Japan, which tells of a 1st grade elementary school girl, who does not yet have a focus on the learning process. Totto-chan doesn't like schools with conventional learning systems. A mother who truly understands her child, tries to find the right school for Totto-chan, and the choice of school is left to the Tomoe Gakuen. This article was written based on a research on moral values in Totto-chan novel. The aims of the study were to describe the moral values contained in the novel and the implementation of each values in the novel especially in the educational field. This study belonged to descriptive qualitative. Because this study involved novel as the main source, reading the novel as a whole was the first step that must be done. The data were moral values. There were 75 data of moral values found in this study. The data obtained in this study coming from the processing of data collection then analyzed and produces a descriptive detail regarding the explanation of the data that had been collected. The result of the study was how we can understand the moral values contained in the novel. There were nine values that are emphasized in this study. Those values were creativity, curiosity, honesty, hardworking, independence, discipline, kindness, tolerance and caring for the environment. The story in the Totto-chan novel, where the main character Totto-chan was the author's first name. So the story raised in this novel was the author's childhood experience. Tetsuko Kuroyanagi, felt the benefits of going to school at Tomoe Gakuen, which was able to emphasize her character better by true educators namely the Principal and founder and owner of the Tomoe Gakuen School. Keyword: Novel, Totto-chan, educationl, moral values, values